Effect of De-Ashing Strategies on Pore Structure and Electrochemical Performance of Activated Carbons for Supercapacitors - Weiwei KANG; Guangxu HUANG; Qianhao GENG; Wentao HOU; Youheng YAO; Bing XU; Baolin XING; Chuanxiang ZHANG (Medžiagotyra, 2018)
The ash was removed before or after carbonization of potassium humate to investigate the effect of ash removal methods on pore structure and electrochemical performance of activated carbons for supercapacitors. The activated carbons were prepared by direct carbonization of potassium humate at 700 ℃ for 1 hour under N2 atmosphere with different de-ashing strategies. It was found that ash removal before carbonization was an effective strategy to reduce the ash content of the corresponding activated carbon. When de-ashing treatment was adopted after carbonization, part of the ash in activated carbon was coated with carbon and could not be removed through acid soaking. Moreover, ash removal before carbonization could better contribute to creating the micropores and the ash removed after carbonization performed as templates to mainly generate mesopores. The activated carbon with ash removed before carbonization as electrodes delivered a specific capacitance of 164.84 F/g at a current density of 50 mA/g, and exhibited typical electric double layer capacitive performance as well as lower leakage current of 15.3 µA. DOI: http://dx.doi.org/10.5755/j01.ms.24.3.18505